Influence of polyelectrolyte architecture on the electrokinetics and dewaterability of industrial membrane bioreactor activated sludge. (1st March 2019) - Yousefi, Shiva A.; Nasser, Mustafa S.; Hussein, Ibnelwaleed A.; Judd, Simon
Abstract: Improvement of sludge dewaterability is greatly hindered by the presence of large amounts of interstitial water molecules trapped in the sludge as a result of strong hydrophilic characteristics. This study has investigated the influence of six different polyacrylamide (PAM) flocculants with different molecular architecture (linear, slightly and highly branched), charge density (CD) and molecular weight (MW) on the electro-kinetics and dewatering of highly stable industrial membrane bioreactor (MBR) sludge. The impact of PAM on flocculation is manifested in the supernatant turbidity, particle zeta potential, sludge capillary suction time (CST), floc size and settleability. Turbidity removal and reduction in zeta potential are used to identify the optimum polymer dose. An optimum dose of 70 mg.L −1 has been determined for linear PAM of 40% CD. However, a highly-branched PAM, with the same CD, has shown an optimum value of 30 mg.L −1 . In all cases, a turbidity removal of more than 99% and CST reduction of 51–64% is attained; the linear PAMs have resulted in the highest CST reduction. Higher PAM doses have resulted in larger flocs and the maximum particle size is observed at the saturation point. The reduction in sludge volume relates with the floc size and PAM dose. For sludge conditioning and dewaterability, highly branched PAM with low MW has shown superior performance over linear high MW PAM. Enhancement of flocculation and dewatering is correlated with the surface charge neutralization and bridging mechanisms. Highlights: Electrokinetics behavior of conditioned Industrial MBR sludge is investigated. Highly branched PAMs showed a better performance at lower optimum dose. Capillary suction time (CST) reduction of 51–64% are attained for the tested PAMs. Sludge percent volume reduction is directly proportional to PAM's MW and dose.